EFFICIENCY OF THE USE OF THE "PENISETUM PURPUREUM" PLANT FOR AN ADEQUATE BALANCE IN THE C / N RELATIONSHIP AS A MEASURE TO CONTROL THE PRODUCTION OF SULF HYDRIC ACID AND THUS PREVENT ENGINE COHERRETIO - Carlos SABORÍO VÍQUEZ (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The results of this study undoubtedly demonstrate that the plant Penisetum purpureum is a plant with great energy potential, and can become a great solution to be used as a source of biomass to produce biogas and therefore for the production of energy electric as an alternative energy source. In this experiment, we have comparatively studied three mixtures of substrate of animal origin (sardinia) and substrate of vegetal origin (Penisetum purpureum), with the purpose of determining the variables corresponding to different proportions in the mixtures taking as parameter the C / N ratio. ; and its incidence in the control and reduction of hydrogen sulfide in the biodigester. Laboratory analyzes were carried out for fresh weight, dry weight, volatile mass and biogas production, methane production and also at the level of a biogas production plant the volume of hydrogen sulfide was analyzed according to the different mixtures proposed. The main objective of this work was to compare the total production of biogas and methane versus the increase in the production of hydrogen sulfide and the control and reduction of this through the use of the species Penisetum purpureum as a contribution of carbon within the C / N ratio.